Developing a causal relationship among factors of e-commerce: A decision making approach - Abdullah, L. (2019)
This study introduces the decision-making trial and evaluation laboratory (DEMATEL) method to develop a causal relationship between factors of e-commerce. Differently from the typical correlation analysis which directly used two groups of variables to measure strength of correlation, this decision making approach develops two groups of factors which are known as cause and effect groups to enhance the significance of e-commerce. A survey approach was used to collect data from a purposeful sampling of undergraduate students at a public university in Malaysia. Empirical data were computed using the seven-step of DEMATEL method where the initial decision matrix was transformed to total relation matrix prior to developing cause and effect diagram. Not only did the DEMATEL unravel the relationship between factors, the DEMATEL method also provides degrees of importance of all factors. The main finding of this study is the visualization of the causal relationship among factors of e-commerce through a digraph, where the factor âinformation about products or servicesâ is mutually influenced by the factors âconvenienceâ âease of use systemâ and âweb reputationâ. E-commerce companies should, however, carefully evaluate the cause and effect factors, and the degree of importance of factors when offering services or products via online. Â© 2019 The Authors